Differential susceptibility of PC12 and BRL cells and the regulatory role of HIF-1α signaling pathway in response to acute methylmercury exposure under normoxia. (1st October 2020) - Liu, Tingting; Gao, Qianqian; Yang, Bobo; Yin, Changsheng; Chang, Jie; Qian, Hai; Xing, Guangwei; Wang, Suhua; Li, Fang; Zhang, Yubin; Chen, Da; Cai, Jiyang; et al.
Highlights: Neuronal PC12 cells were more sensitive than BRL cells to the toxicity of MeHg. MeHg decreased HIF-1α at a lower concentration in PC12 cells than in BRL cells. Up-regulation of HIF-1α attenuated the toxicity of MeHg in both cell lines. Abstract: Hypoxia-inducible factor 1 (HIF-1) is a critical nuclear transcription factor for adaptation to hypoxia; its regulatable subunit, HIF-1α, is a cytoprotective regulatory factor. We examined the effects of methylmercury (MeHg) in rat adrenal pheochromocytoma (PC12) cells and the rat hepatocyte cell line BRL. MeHg treatment led to time- and concentration-dependent toxicity in both lines with statistically significant cytotoxic effects at 5 μM and 10 μM in PC12 and BRL, respectively, at 0.5 h. HIF-1α protein levels were significantly decreased at 2.5 (PC12) and 5 (BRL) μM MeHg. Furthermore, MeHg reduced the protein levels of HIF-1α and its target genes ( glucose transporter-1, vascular endothelial growth factor-A and erythropoietin ). Overexpression of HIF-1α significantly attenuated MeHg-induced toxicity in both cell types. Notably, cobalt chloride, a pharmacological inducer of HIF-1α, significantly attenuated MeHg-induced toxicity in BRL but not PC12. In both cell lines, an inhibitor of prolyl hydroxylase, 3, 4-dihydroxybenzoic acid, and the proteasome inhibitor carbobenzoxy-L-leucyl-L-leucyl-L-leucinal(MG132), antagonized MeHg toxicity, while 2-methoxyestradiol, a HIF-1α inhibitor, significantly increased it. These data establish that: (a) neuron-like PC12 cells are more sensitive to MeHg than non-neuronal BRL cells; (b) HIF-1α plays a similar role in MeHg-induced toxicity in both cell lines; and (c) upregulation of HIF-1α offers general cytoprotection against MeHg toxicity in PC12 and BRL cell lines.